(untitled) (Swiss Medical Weekly, 2022)
BACKGROUND AND PURPOSE: Culturally diverse countries such as Switzerland face the challenge of providing cross-cultural competent care. Cross-cultural competent care needs an understanding of a patient’s cultural context in order to provide safe and effective care. Therefore, we sought to examine cross-cultural competence of Swiss paediatric oncology care providers, and to explore their perceptions of barriers to and facilitators of cross-culturally competent care. DESIGN AND SAMPLE: We conducted a cross-sectional study. The data collection period was three weeks. Providers were recruited through collaborators at the participating paediatric oncology centres. All occupational groups who are in direct contact with patients and involved in their care were eligible (e.g., physicians, nurses, social workers, occupational therapists and physiotherapists). Surveying providers online, we captured five subscales of their cross-cultural competence and their perceptions as to how to facilitate cross-culturally competent paediatric oncology care. We employed the Cross-Cultural Competence of Healthcare Professionals (CCCHP) questionnaire. Besides descriptive and inferential statistics, we performed content analysis. FINDINGS: The response rate was 73.2% (n = 183/250). Analyses revealed differences in cross-cultural competence between occupational groups of paediatric oncology providers. Overall, social workers’ cross-cultural competence was higher than nurses’ or occupational therapists’ and physiotherapists’ cross-cultural competence. Physicians’ cross-cultural competence was higher than nurses (with no statistically significant difference identified between physicians, occupational therapists and physiotherapists). Furthermore, our results suggest noteworthy differences among the four main occupational groups on the five CCCHP subscales. Physicians and social workers declared more positive attitudes than nurses; occupational therapists and physiotherapists reported lower skills than the other three groups; social workers scored higher on the emotions and empathy subscale than the other three groups; physicians were more knowledgeable and aware than nurses. Most frequently mentioned barriers were: language barriers (68.5%), different culture and values (19.2%), different illness understanding (9.2%). Most frequently mentioned facilitators were: professional translators (47.2%), continuous training (20.8%), professional cultural mediators (8.8%). CONCLUSIONS/IMPLICATIONS: Trainings and interventions are widely considered a principal strategy to advance providers’ cross-cultural competence. Our findings of differences in cross-cultural competence among occupational groups further underpin the need to adapt training programmes and interventions to the respective occupational group and the respective dimension(s) of cross-cultural competence. In addition, professional translators and cultural mediators should be used. Lastly, reciprocal supervision and the promotion of multidisciplinary teams is crucial to enable oncology care providers to learn from each other and this exchange could also help to reduce some of the differences between the various occupational groups.